2019
DOI: 10.1002/jppr.1457
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of medication prescription by dementia diagnosis in Australian nursing home residents: a cross‐sectional study

Abstract: Background Current information on the patterns of medication use in nursing home residents living with dementia is conflicting. Aim The aim of this study was to investigate medication use and its associations with dementia diagnosis in Australian nursing home residents. Methods A cross‐sectional study of 541 residents from 17 Australian nursing homes was performed. Results Over 12 months, nursing home residents were prescribed a mean (±SD) of 14.5 ± 6.8 medications each. Approximately 95% of residents were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…We found that, except for antiplatelets, people with Alzheimer's disease were less frequently dispensed medicines for cardiovascular conditions than the age‐ and gender‐matched comparison group. Our findings align with a previous Australian study involving 546 nursing home residents, which found that people with dementia were less likely to be prescribed medicines for cardiovascular and respiratory diseases than residents without dementia (adjusted odds ratio 0.45, 95% confidence interval 0.27–0.77, p=0.003) . It is unclear whether the lower prevalence of medicines used for cardiac conditions in people with Alzheimer's disease reflects appropriate treatment due to a lower prevalence of cardiovascular conditions in people with Alzheimer's disease or if it reflects a possible undertreatment of cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 83%
“…We found that, except for antiplatelets, people with Alzheimer's disease were less frequently dispensed medicines for cardiovascular conditions than the age‐ and gender‐matched comparison group. Our findings align with a previous Australian study involving 546 nursing home residents, which found that people with dementia were less likely to be prescribed medicines for cardiovascular and respiratory diseases than residents without dementia (adjusted odds ratio 0.45, 95% confidence interval 0.27–0.77, p=0.003) . It is unclear whether the lower prevalence of medicines used for cardiac conditions in people with Alzheimer's disease reflects appropriate treatment due to a lower prevalence of cardiovascular conditions in people with Alzheimer's disease or if it reflects a possible undertreatment of cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 83%
“…These are key indicators of medication use quality, given the well-documented risk of harm associated with these medicines, the high prevalence of dementia and potentially problematic psychotropic agent use in Australian RACF. 29,30 Reducing the number of prescribed medications was a similar outcome reported in a recent systematic review evaluating outcomes of medication reviews in RACF residents both with and without dementia. 36 Multi-faceted interventions, inclusive of collaborative pharmacist-led medication reviews in residents both with and without dementia, have demonstrated efficacy in reducing inappropriate psychotropic medication use.…”
Section: Discussionmentioning
confidence: 70%
“…Further, residents with dementia are often managed with complex multi‐drug regimens inclusive of several psychotropic drugs 24 . RACF residents with dementia are three‐fold more likely to be prescribed antipsychotics compared with persons with dementia residing in the community, and nine‐fold more likely to be prescribed an antipsychotic than RACF residents without dementia 28,29 . Psychotropic drug use in residents with dementia is associated with reduced quality of life and increased adverse outcomes, including stroke, falls, hospital admissions and mortality 30 …”
Section: Introductionmentioning
confidence: 99%
“…Residents of care facilities frequently have low serum vitamin D which has been associated with depression, so increased time spent outdoors may improve mood by increasing vitamin D [23,27]. In this study 31% of participants were receiving vitamin D supplementation so adjustments were made in analyses for vitamin D prescription [28]. Given existing recommendations for prescription of vitamin D in adults residing in aged care homes, this rate appears low [29,30].…”
Section: Discussionmentioning
confidence: 97%